Oral Drugs Against COVID-19: Management of Drug Interactions With the Use of Nirmatrelvir/Ritonavir. - Mikus, Gerd; Foerster, Kathrin I.; Terstegen, Theresa; Vogt, Cathrin; Said, André; Schulz, Martin; Haefeli, Walter E. (Deutsches Ärzteblatt International, 2022)
Background: Five-day oral therapies against early COVID-19 infection have recently been conditionally approved in Europe. In the drug combination nirmatrelvir + ritonavir (nirmatrelvir/r), the active agent, nirmatrelvir, is made bioavailable in clinically adequate amounts by the additional administration of a potent inhibitor of its first-pass metabolism by way of cytochrome P450 [CYP] 3A in the gut and liver. In view of the central role of CYP3A in the clearance of many different kinds of drugs, and the fact that many patients with COVID-19 are taking multiple drugs to treat other conditions, it is important to assess the potential for drug interactions when nirmatrelvir/r is given, and to minimize the risks associated with such interactions. Methods: We defined the interaction profile of ritonavir on the basis of information derived from two databases (Medline, GoogleScholar), three standard electronic texts on drug interactions, and manufacturer-supplied drug information. We compiled a list of drugs and their potentially relevant interactions, developed a risk minimization algorithm, and applied it to the substances in question. We also compiled a list of commonly prescribed drugs for which there is no risk of interaction with nirmatrelvir/r. Results: Out of 190 drugs and drug combinations, 57 do not need any special measures when given in combination with brief, low-dose ritonavir treatment, while 15 require dose modification or a therapeutic alternative, 8 can be temporarily discontinued, 9 contraindicate ritonavir use, and 102 should preferably be combined with a different treatment. Conclusion: We have proposed measures that are simple to carry out for the main types of drug that can interact with ritonavir. These measures can be implemented under quarantine conditions before starting a 5-day treatment with nirmatrelvir/r.